PENGARUH PEMBELAJARAN ADAPTIF WAWASAN NUSANTARA TERHADAP PEMBENTUKAN KARAKTER NASIONALISME - Siregar, Paulina; Sulistyowati, Sri; Suhartini (JURNAL DWIJA KUSUMA, 2024)
Abstract The Covid-19 pandemic has brought many changes to people's lives in almost every activity, including education. Educational institutions are required to create a new culture in providing learning for their students. The current fact is that the younger generation is starting to lose its nationalist character. The decline in the character of nationalism is thought to be due to cultural changes that occurred as a result of the Covid-19 pandemic. This can be seen from the emergence of cases of brawls that occur between students and even the community, sometimes resulting in fatalities, the rise in bullying cases that occur among junior high school students and suicide cases among the younger generation. News These cases show how fragile the condition of the nation's next generation is. . This adaptive education is one way to bridge the gap that has arisen as a result of distance education implemented due to the Covid-19 pandemic. This adaptive education places greater emphasis on involvement in daily activities as a learning process. The research method used is the sequential exploratory method, namely collecting and analyzing qualitative data then collecting and analyzing quantitative data. In order to support quantitative data analysis, this research also applies qualitative data analysis techniques to analyze data from interviews and literature studies. The results of this research show that adaptive learning of Indonesian insight has a significant effect on the formation of nationalistic character with a correlation coefficient of R = 0.366. Where the influencing factors from internal and external are related to learning of Indonesian insight material which is the implementation of daily behavior.